Desain Pengembangan Kurikulum Di Pesantren Miftahul Ulum Kecamatan Penarik Mukomuko - Daraqthuni Daraqthuni (JPT : Jurnal Pendidikan Tematik, 2024)
Educational institutions that can organize formal and non-formal and even informal learning at the same time are pesantren. In its history, the direct relationship between the pesantren environment, family and community and even the state has been going on for approximately four centuries. What is then needed by pesantren is to formulate a clear curriculum that is able to cover all forms and environments of education. The effort has been made by Pesantren Miftahul Ulum, Penarik District, Mukomuko. This investigation aims to describe the curriculum development pattern of the pesantren. The method of investigation used was a case study. Data were obtained from interviews, observations and document studies. The results of the investigation show that the development of pesantren curriculum must still take into account the quality of the curriculum both in the planning, control and reinforcement stages. The basic character of the curriculum can be based on the character of ulul albâb believers, which has historically been the main vision of pesantren since the 17th century. The character is integrated in the form of pesantren learning, recitation, and the real life of the santri, ustadz, and kiai (care pattern of boarding school).